Biomimetic anchors for antifouling and antibacterial polymer brushes on stainless steel - Yang, Wen Jing (Langmuir : the ACS journal of surfaces and colloids, 2011)
Barnacle cement (BC) was beneficially applied on stainless steel (SS) to serve as the initiator anchor for surface-initiated polymerization. The amine and hydroxyl moieties of barnacle cement reacted with 2-bromoisobutyryl bromide to provide the alkyl halide initiator for the surface-initiated atom transfer radical polymerization (ATRP) of 2-hydroxyethyl methacrylate (HEMA). The hydroxyl groups of HEMA polymer (PHEMA) were then converted to carboxyl groups for coupling of chitosan (CS) to impart the SS surface with both antifouling and antibacterial properties. The surface-functionalized SS reduced bovine serum albumin adsorption, bacterial adhesion, and exhibited antibacterial efficacy against Escherichia coli (E. coli). The effectiveness of barnacle cement as an initiator anchor was compared to that of dopamine, a marine mussel inspired biomimetic anchor previously used in surface-initiated polymerization. The results indicate that the barnacle cement is a stable and effective anchor for functional surface coatings and polymer brushes